Educação ambiental na formação cidadã: aspectos históricos e pontuais - SANTOS, Maria Tânia Costa dos (2020)
In this bibliographic analysis, the main reason for the emblematic theme on Environmental Education reveals that the citizen training seeks identification to originate environmental awareness, whose objectives are to transform the subject into an ethical and citizen being in formal spaces and away from school walls, removing unethical and anti-citizen attitudes offensive to the environment, transferring the harmfulness of the subject into citizenship for himself and for other human beings. Fostering in EE is globalized and transversal because it is within each mind; being in this, supported the objectives that begin this work, like object to be researched in an environment where the man has influenced in a disharmonic process. The arrangements of this work were sustained in a theoretical pillar ranked by the quality of its contributions. The currents that I defend and consider precise give essentiality to this research; in a wallpaper with subjectively reflective edges and simultaneously appealing to an immediate sensitization and affection towards life; besides the understanding of education that is described as educational practice in the perspective of citizenship; as an expected result in the rights and obligations to be borne by the system. And to put into practice the observances existing in the direction that has been regulated, will free us, by the hour, from our historically instilled oppressions; because it depends on a joint action to solemnly take care of a graduation that will breed in a generation responsible for bringing social, personal, economic, political, cultural, ecological, ethical, etc. formation as a dimension of the culture of education.